Vertical birth: return to an ancestral tradition - Calderón, Jorge (2015)
OBJECTIVE: To determine the advantages of vertical childbirth over supine confinement. DESIGN: Observational, comparative and cross sectional study. SETTING: Hospital Nacional Edgardo Rebagliati Martins, EsSalud, Lima, Peru, a medical residency hospital. Participants: Pregnant women who had either vertical or supine childbirth. INTERVENTIONS: We studied 160 women from June 2006 through June 2007; 80 had vertical delivery and 80 supine childbirth. Main outcome measures: Time of delivery, uterine bleeding volume, episiotomy need, complications, maternal perception. RESULTS: Time for third stage of labor was shorter in vertical versus supine confinement (11,39 versus 19,48 minutes respectively). Average bleeding volume was similar in both groups (300 mL and 296,74 mL respectively). Considering the use and non-use of post partum oxytocin, significant higher bleeding volume was encountered when oxytocin was not used in both groups. Kristeller’s maneuver was hardly necessary for vertical delivery (1,3%) but it was performed in 16 patients with supine childbirth (20%). Episiotomy need was less for vertical delivery (26,5% and 56,3 respectively). Instrumental delivery was required in two supine childbirth cases (1 vacuum, 1 output forceps). There was one case of vaginal hematoma and one postpartum hemorrhage with supine childbirth, with no statistical significance. There were more vaginal superficial tears in the vertical delivery group when episiotomy was not done (83% and 60% respectively). Mothers perceived vertical birth as faster, more comfortable and less painful; they enjoyed seeing their babies being born (96,3% vs. 42,5% respectively) and vertical childbirth was recommended by most women from both groups (81,9% of the 160 women). CONCLUSIONS: Vertical delivery offers significant advantages compared to supine confinement with shorter third stage of labor, less pain, more comfort, and most rewarding.